1986
DOI: 10.1111/j.1346-8138.1986.tb02894.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Selenium on Mice Inoculated with B16 Melanoma Cells

Abstract: The influence of selenium dioxide on the in vitro and in vivo growth of transplantable B16 melanoma was studied. In the in vivo study, melanoma tissues showed a decrease in development of tumor growth and a tendency toward higher levels of free radical signal (ESR). Cultured B16 melanoma cells revealed a marked disturbance of cell growth especially in the solution with a high dose of selenium. These results may indicate that selenium has an antitumorigenic effect on B16 melanoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Recent studies have described chemopreventive agents exhibiting low toxicity by systematic administration and preventing both the onset and metastasis of primary melanoma (Rodriguez‐Vicente et al, 1998; Bialy et al, 2002). Specific selenium compounds, when added to cell culture systems or as supplements in animal diets, reduce cell proliferation and the incidence and severity of cancer in vivo (Hanada et al, 1986; Yan et al, 1997, 1999; Waters et al, 2003). Several research groups have searched for active Se metabolites of low toxicity, but with the ability to induce apoptosis, in the hope that such compounds might have valuable chemopreventive activities (Thompson et al, 1994; Jiang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have described chemopreventive agents exhibiting low toxicity by systematic administration and preventing both the onset and metastasis of primary melanoma (Rodriguez‐Vicente et al, 1998; Bialy et al, 2002). Specific selenium compounds, when added to cell culture systems or as supplements in animal diets, reduce cell proliferation and the incidence and severity of cancer in vivo (Hanada et al, 1986; Yan et al, 1997, 1999; Waters et al, 2003). Several research groups have searched for active Se metabolites of low toxicity, but with the ability to induce apoptosis, in the hope that such compounds might have valuable chemopreventive activities (Thompson et al, 1994; Jiang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…69 Several studies have also shown inhibitory effects on melanoma growth and spread in animals using low doses. [70][71][72][73] Melanoma patients have significantly lower serum selenium levels than do healthy controls, and the decrease relates directly to the severity of their disease and rate of recurrence. 74,75 I would recommend 200 to 400 µg/d of selenomethionine.…”
Section: Seleniummentioning
confidence: 99%
“…Epidemiological studies conducted over the past 40 years examining the relationship between dietary intake of Se and total cancer risk have been somewhat controversial. In addition, numerous in vivo studies have showed that dietary supplementation with Se reduces cancer incidence in a variety of animal models including a model of mouse melanoma [Hanada et al, 1986] and models of cancer of the colon [Wattenberg, 1974; Temple and Basu, 1987], breast [Schrauzer et al, 1976; Watrach et al, 1984; el‐Bayoumy, 1994], liver [Yu et al, 1988; Bansal et al, 1990; Popova, 2002], esophagus [Guttenplan et al, 2002], kidney [Schroeder and Mitchener, 1972; Poirier and Milner, 1983], and lung [Liu et al, 1987; el‐Bayoumy et al, 1993; Prokopczyk et al, 1997, 2000]. Table I lists four ecological studies that were conducted that showed an inverse relationship between intake of dietary Se and overall cancer risk.…”
Section: Epidemiologic and Retrospective Studies Of Se And Cancermentioning
confidence: 99%